The Role of Risk Management as an Organizational Management Strategy: A Literature Study - Ameilia Nurfadhilah; Fitria Aulia Cahyaningrum; Ahmad Dairobi; Janu Ilham Saputro (Takaza Innovatix Labs Ltd., 2026)
This study explores the strategic role of risk management in enhancing organizational performance amid increasing uncertainty. The research aims to analyze how risk management contributes to performance improvement through systematic implementation across various organizational contexts. Using a qualitative method with a literature review design, data were obtained from national and international journals, reference books, and risk management frameworks such as ISO 31000 and COSO ERM published in the past ten years. Thematic analysis was employed to identify patterns, practices, and key factors influencing successful implementation. The findings show that organizations applying structured risk management—from identification, analysis, evaluation, control, to monitoring—achieve higher stability, improved decision-making, and stronger stakeholder trust. The study concludes that risk management is not only a defensive measure but also a strategic tool that supports sustainability and competitive advantage.